The immunoproteasome and viral infection: a complex regulator of inflammation - McCarthy, Mary K.; Weinberg, Jason B. (Frontiers in Microbiology, 2015)
During viral infection, proper regulation of immune responses is necessary to ensure successful viral clearance with minimal host tissue damage. Proteasomes play a crucial role in the generation of antigenic peptides for presentation on MHC class I molecules, and thus activation of CD8 T cells, as well as activation of the NF-kB pathway. A specialized type of proteasome called the immunoproteasome is constitutively expressed in hematopoietic cells and induced in nonimmune cells during viral infection by interferon (IFN) signaling. The immunoproteasome regulates CD8 T cell responses to many viral epitopes during infection. Accumulating evidence suggests that the immunoproteasome may also contribute to regulation of proinflammatory cytokine production, activation of the NF-kB pathway, and management of oxidative stress. Many viruses have mechanisms of interfering with immunoproteasome function, including prevention of transcriptional upregulation of immunoproteasome components as well as direct interaction of viral proteins with immunoproteasome subunits. A better understanding of the role of the immunoproteasome in different cell types, tissues, and hosts has the potential to improve vaccine design and facilitate the development of effective treatment strategies for viral infections.